Altered pathways of keratinization, extracellular matrix generation, angiogenesis, and stromal stem cells proliferation in patients with systemic sclerosis. Issue 2 (June 2023) - Spinella, Amelia; Lo Tartaro, Domenico; Gibellini, Lara; de Pinto, Marco; Pinto, Valentina; Bonetti, Elisa; Lolli, Francesca; Lattanzi, Melba; Lumetti, Federica; Amati, Gabriele; De Santis, Giorgio; Cossarizza, Andrea; et al.
Objective: Systemic sclerosis is characterized by endothelial dysfunction, autoimmunity abnormalities, and fibrosis of the skin and internal organs. The pathogenetic mechanisms underlying systemic sclerosis vasculopathy are still not clarified. A complex cellular and extracellular network of interactions has been studied, but it is currently unclear what drives the activation of fibroblasts/myofibroblasts and the extracellular matrix deposition. Methods: Using RNA sequencing, the aim of the work was to identify potential functional pathways implied in systemic sclerosis pathogenesis and markers of endothelial dysfunction and fibrosis in systemic sclerosis patients. RNA-sequencing analysis was performed on RNA obtained from biopsies from three systemic sclerosis patients and three healthy controls enrolled in our University Hospital. RNA was used to generate sequencing libraries that were sequenced according to proper transcriptomic analyses. Subsequently, we performed gene set enrichment analysis of differentially expressed genes on the entire list of genes that compose the RNA-sequencing expression matrix. Results: Gene set enrichment analysis revealed that healthy controls were characterized by gene signatures related to stromal stem cells proliferation, cytokine–cytokine receptor interaction, macrophage-enriched metabolic network, whereas systemic sclerosis tissues were enriched in signatures associated with keratinization, cornification, retinoblastoma 1 and tumor suppressor 53 signaling. Conclusion: According to our data, RNA-sequencing and pathway analysis revealed that systemic sclerosis subjects display a discrete pattern of gene expression associated with keratinization, extracellular matrix generation, and negative regulation of angiogenesis and stromal stem cells proliferation. Further analysis on larger numbers of patients is needed; however, our findings provide an interesting framework for the development of biomarkers useful to explore potential future therapeutic approaches.